2010
DOI: 10.1097/aln.0b013e3181c62d43
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Critical Intraoperative Event Management Skills in Novice Anesthesiology Residents by Using High-fidelity Simulation-based Training

Abstract: Event-specific, simulation-based training resulted in superior performance in scenarios compared with traditional training and simulation-based training in an alternate event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 24 publications
1
45
0
2
Order By: Relevance
“…Park et al 69 have shown that the improvements observed following simulation-based training appear to be content specific. In their study with anesthesia residents, they demonstrated that event-specific simulation training resulted in subsequent improved performance compared with simulation-based training in an alternate event.…”
Section: Debriefingmentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al 69 have shown that the improvements observed following simulation-based training appear to be content specific. In their study with anesthesia residents, they demonstrated that event-specific simulation training resulted in subsequent improved performance compared with simulation-based training in an alternate event.…”
Section: Debriefingmentioning
confidence: 99%
“…According to the research to date, the format in which debriefing is delivered (simulation-based, instructor-led, multimedia, or self-led instruction) does not seem to impact learning. However, the work of researchers, such as Johnson et al 70 and Park et al, 69 suggests that the content and the structure of the debriefing or feedback may play an important role in learning.…”
Section: Debriefingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies included between five and 28 experts in the Delphi process. 8,9,10 We achieved good internal consistency providing a high degree of confidence in our sample size of 10 experts.To address the issue of content validity we aimed to achieve consensus amongst a group of experts using a Delphi process. The concordance achieved was 0.668.…”
mentioning
confidence: 99%
“…This technique has been used previously to develop simulation-based assessment tools. 8,9,10 A draft list of tasks deemed necessary to successfully perform spinal anaesthesia for caesarean delivery and manage the complication of hypotension progressing to cardiac arrest was developed by two anaesthetic specialists. The list of tasks was distributed to 10 anaesthetic specialists working at the study site -all involved in intern, medical officer and registrar training for obstetric anaesthesia.…”
Section: The Modified Delphi Processmentioning
confidence: 99%